High adhesion uvioresistant polyester powder coating and method for its preparation

CN121249246BActive Publication Date: 2026-10-23ZHEJIANG LVHUAN NEW MATERIAL TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202511814546.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-12-04
Publication Date
2026-10-23
Estimated Expiration
2045-12-04

AI Technical Summary

Technical Problem

现有的饱和/不饱和聚酯树脂提供良好的力学性能,适用于室内装饰;但在户外应用中,UV辐射诱导酯键光氧化,导致链断裂、黄变及脆化;因此现有聚酯粉末涂料体系在追求高性能方面仍面临技术挑战

Benefits of technology

1、本发明通过精妙的分子结构设计,有效解决传统聚酯涂料中硬度与韧性难以兼得的矛盾。本发明中对苯二甲酸提供刚性的芳香骨架,确保涂膜的高硬度和耐刮擦性;同时引入十二烷二酸长链脂肪酸,其柔性链段作为内增塑剂,有效降低聚酯主链的玻璃化转变温度和内应力;其次通过分步酯交换引入的端羟基聚二甲基硅氧烷形成柔性侧链或软嵌段结构;通过刚性芳香骨架、长链脂肪酸柔性和有机硅侧链缓冲的多重柔性协同机制,使得在受到外力冲击时,应力能被有效地传递和耗散,避免了应力集中导致的主链断裂,远超无柔性组分或结构单一的现有技术体系。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121249246B_ABST
    Figure CN121249246B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of powder coating, in particular to a high-adhesion ultraviolet-resistant polyester powder coating and a preparation method thereof.The present application overcomes the problem that the mechanical properties and ultraviolet resistance of the polyester powder coating cannot be considered simultaneously in the prior art.The present application first esterifies and polycondensates terephthalic acid, isophthalic acid and dodecanedioic acid with neopentyl glycol and trimethylolpropane;hydroxyl-terminated polydimethylsiloxane and reactive UVA are introduced step by step in the polycondensation process, and are covalently bonded to the polyester main chain through chemical reaction;finally, trimellitic anhydride is used for end-capping to obtain a modified polyester resin;the modified polyester resin is mixed with HAA, HALS and inorganic fillers pretreated by an epoxy-based silane coupling agent to obtain the powder coating.The coating realizes the improvement of the mechanical properties through the synergistic effect of the components and the process, while maintaining good ultraviolet resistance, significantly improving the comprehensive durability of the powder coating, and is suitable for high-durability outdoor coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of powder coating technology, specifically to a high-adhesion UV-resistant polyester powder coating and its preparation method. Background Technology

[0002] Powder coatings are widely used in industrial coatings due to their environmental friendliness, high utilization rate, and excellent performance. Existing saturated / unsaturated polyester resins offer good mechanical properties, making them suitable for interior decoration; however, in outdoor applications, UV radiation induces photo-oxidation of ester bonds, leading to chain breakage, yellowing, and embrittlement. Therefore, existing polyester powder coating systems still face technical challenges in pursuing high performance.

[0003] Traditional aromatic polyesters, including polyester materials based on terephthalic acid, offer high hardness and weather resistance, but their rigid skeleton leads to high internal stress and brittleness. The impact strength and bending resistance of the coating are often poor. To improve flexibility, long-chain fatty acids or flexible polyols need to be introduced, but this usually comes at the cost of hardness and chemical resistance.

[0004] In addition, in outdoor applications, commonly used UV absorbers and hindered amine light stabilizers are mostly non-reactive additives. They are added to the coating through physical mixing. Under long-term outdoor exposure and temperature changes, these non-reactive additives are prone to migration, precipitation and volatilization, resulting in a decrease in protective effect, rapid chalking and yellowing of the coating, and a sharp decline in mechanical properties.

[0005] In summary, existing technologies achieve balanced performance control by modifying the powder coating matrix or adding additives; however, they still struggle to effectively address the inability to simultaneously achieve both mechanical properties and UV resistance.

[0006] To address this, a high-adhesion UV-resistant polyester powder coating and its preparation method are proposed. Summary of the Invention

[0007] The purpose of this invention is to provide a high-adhesion, UV-resistant polyester powder coating and its preparation method. The invention first involves esterification and polycondensation of terephthalic acid, isophthalic acid, dodecanoic acid, neopentyl glycol, and trimethylolpropane. During the polycondensation process, hydroxyl-terminated polydimethylsiloxane and reactive UVA are introduced stepwise, covalently bonded to the polyester backbone through a chemical reaction. Finally, trimellitic anhydride is used for end-capping to obtain a modified polyester resin. This modified resin is then mixed with HAA, HALS, and inorganic fillers pretreated with epoxy silane coupling agents to obtain the powder coating. This coating, through the synergistic effect of its components and process, improves mechanical properties while maintaining good UV resistance, significantly enhancing the overall durability of the powder coating and making it suitable for high-durability outdoor coatings.

[0008] To achieve the above objectives, the present invention provides the following technical solution: This invention provides a method for preparing a high-adhesion, UV-resistant polyester powder coating, comprising the following steps: Add 300 parts of rutile titanium dioxide and 20-30 parts of precipitated barium sulfate to a high-speed mixer with a cooling jacket, and disperse by stirring at 500-800 rpm. Start the cooling system and control the temperature to not exceed 40℃ to obtain inorganic filler. Slowly and evenly add 5-8 parts of epoxy silane coupling agent to the high-speed rotating filler vortex using a peristaltic pump, controlling the addition time to 5-8 minutes, and maintain stirring at 500-800 rpm for 5-10 minutes to obtain treated filler. Add 580-620 parts of modified polyester resin, 30-35 parts of HAA, 3-8 parts of HALS, and polyacrylate leveling agent WL-3090 to the treated filler. Add 5 parts of benzoin and 5 parts of other ingredients to a high-speed mixer at 1000-1500 rpm and premix for 3-5 minutes, maintaining the mixer temperature at 35-40℃ to obtain a powder system. Feed the powder system evenly into a co-rotating twin-screw extruder (L / D=40, divided into 9 sections). Control the temperature of the feeding zone at 30-40℃; the melting zone at 80-95℃; and the homogenization zone at 95-110℃, always keeping these temperatures below the curing initiation temperature of the resin / HAA system. The temperature is 10℃; the die temperature is 100℃; the screw speed is 300-500rpm, the extrusion rate is maintained at 5-10kg / h, the pressure is 5-8MPa, and the total residence time is 30-60s to obtain a molten system; the molten system is pressed into sheets by water-cooled rollers at 10-15℃ to obtain sheets with a thickness of 1-2mm; then it is added to a grinding mill at 8000rpm and filtered through a 140-mesh screen; then it is subjected to magnetic separation to remove iron, maintaining a particle size D50 of 35-45μm to obtain a polyester powder coating.

[0009] Preferably, the preparation of the modified polyester resin includes the following steps: Add 350-400 parts of terephthalic acid, 100-150 parts of isophthalic acid, and 30-50 parts of dodecanoic acid to the esterification reactor and stir until homogeneous. Then, add 350-400 parts of neopentyl glycol, 8-15 parts of trimethylolpropane, and 1-2 parts of stannous oxalate while stirring at 200-300 rpm. Purge with high-purity nitrogen (flow rate 0.5-1 L / min) and purge the gas for 3-5 minutes, achieving a replacement rate >99%. Continue the process at a programmed rate of 5-10 °C / min. Heat the temperature to 210-230℃ and maintain the esterification reaction for 2-4 hours until the material is completely clear and transparent. A sample should be taken and the acid value should be <10mgKOH / g. At this point, the material has become a clear and transparent melt, and the reaction system is obtained. Cool the reaction system to 190℃ at a rate of 3-5℃ / min. Under 200rpm conditions, slowly add 15-30 parts of terminal hydroxyl polydimethylsiloxane dropwise using a peristaltic pump over a total addition time of 20-40 minutes. After the addition is complete, add reactive UVA. 15-30 parts were subjected to transesterification at 200℃ and 250 rpm for 1-2 hours under nitrogen protection. The melt was clarified to obtain a mixed system. The mixed system was then heated from 200℃ to 235-240℃ at a rate of 2-3℃ / min, and a vacuum was applied for 30-60 minutes under stirring at 300 rpm. The vacuum degree was gradually decreased from -0.02 MPa and kept below -0.095 MPa to induce polycondensation. At 200℃, the viscosity of the system was measured using a Brookfield rotational viscometer to be 2500-3500 mPa·s. The acid value of the sample was <5 mg K₂O. H / g, to obtain condensation product; stop vacuum holding of condensation product, introduce nitrogen protection, cool to 180-190℃ at a rate of 5℃ / min, add 45-55 parts of trimellitic anhydride under stirring at 200rpm, increase the speed to 300rpm, keep the reaction at the temperature for 30-60min, take a sample to test the acid value of 30-35mgKOH / g, stop the reaction, pressurize with nitrogen to quickly discharge to a cooling tablet press, use discharge roller, control the roller temperature at 10-15℃, quench into sheets, maintain the thickness of 2-3mm, crush the sheet to 1-2mm, and store in nitrogen-sealed storage to obtain modified polyester resin; The present invention also provides a high-adhesion UV-resistant polyester powder coating, comprising rutile titanium dioxide, precipitated barium sulfate, epoxy silane coupling agent, modified polyester resin, HAA, HALS and additives.

[0010] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. This invention effectively solves the contradiction of achieving both hardness and toughness in traditional polyester coatings through ingenious molecular structure design. In this invention, terephthalic acid provides a rigid aromatic skeleton, ensuring high hardness and scratch resistance of the coating film; simultaneously, the introduction of dodecanoic acid long-chain fatty acid, whose flexible segments act as internal plasticizers, effectively reducing the glass transition temperature and internal stress of the polyester main chain; secondly, the introduction of hydroxyl-terminated polydimethylsiloxane through stepwise transesterification forms flexible side chains or soft block structures; through a multi-flexible synergistic mechanism of rigid aromatic skeleton, flexible long-chain fatty acid, and silicone side chain buffering, stress can be effectively transferred and dissipated under external impact, avoiding main chain breakage caused by stress concentration, far exceeding existing technologies without flexible components or with simple structures.

[0011] 2. This invention constructs a high-density, uniform chemical cross-linking network through precise branching degree control and high acid value regulation, thereby improving the bending resistance of the coating film. In this invention, trimethylolpropane (TMP) is used as a trifunctional monomer to introduce appropriate branching points in the early stage of polymerization, breaking the linear structure and providing three-dimensional support for the formation of the network after curing. Subsequently, trimellitic anhydride is used for precise end-capping at the polymerization end to ensure sufficient and uniform active cross-linking sites when reacting with the curing agent. This synergistic effect of TMP branching and TMA end-capping provides intrinsic stability and three-dimensional support by constructing a dense cross-linking network, while restricting the relative displacement of molecular chain segments. When the coating film is subjected to bending stress, it can effectively disperse stress, prevent the propagation of microcracks, and improve the bending strength.

[0012] 3. This invention successfully solves the problems of migration, precipitation, and failure of traditional non-reactive UV absorbers in long-term outdoor applications through a stepwise polymerization process. During the transesterification stage of polyester resin synthesis, reactive UVA is introduced, anchoring it to the polyester backbone via covalent bonds. This chemically bonded anchoring mechanism prevents UVA migration and volatilization caused by heat, light, or solvents. The synergistic introduction of HALS (Hydrogen Alternating Current) effectively removes free radicals generated by photo-oxidation, forming a dual protection mechanism of UV absorption and free radical scavenging, ensuring the long-term durability of the coating under extreme outdoor conditions.

[0013] 4. This invention significantly improves the adhesion and durability of the coating film through a synergistic strategy of organosilicon modification and inorganic filler surface treatment. First, hydroxyl-terminated polydimethylsiloxane is introduced into the polyester side chains through transesterification. Its inherent low surface energy significantly enhances the wetting and spreading ability of the powder melt on the substrate, optimizes the initial interfacial contact, and improves adhesion at room temperature. An epoxy-based silane coupling agent is used to pretreat the inorganic filler. The coupling agent forms a uniform active layer on the filler surface and, during curing, covalently bonds with the polyester matrix through epoxy groups, achieving chemical bridging between the filler, resin, and substrate. This effectively transfers impact stress from the resin to the filler for dissipation, exhibiting excellent bonding stability under humid and hot conditions. Attached Figure Description

[0014] Figure 1 The graph shows the change in impact strength retention rate of the powder coatings prepared in Examples 1, 6-8, and 10-13 of this invention as a function of light exposure time. Detailed Implementation

[0015] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0016] The epoxy silane coupling agent of this invention is KH-560, γ-glycidyl etheroxypropyltrimethoxysilane, CAS number 2530-83-8; HALS is light stabilizer 622, CAS number 65447-77-0; HAA is β-hydroxyalkylamide, CAS number 55566-30-8; reactive UVA is 3-(2-benzotriazolyl)-4-hydroxy-5-tert-butylphenylpropionic acid, CAS number 84268-36-0; the rutile titanium dioxide has a D50 particle size of 0.2-0.35 μm and its surface is treated with silica inorganically; the precipitated barium sulfate is orthorhombic with a D50 particle size of 0.5-0.8 μm; the hydroxyl-terminated polydimethylsiloxane is a polydimethylsiloxane with double-sided hydroxyl-terminated ends, a number-average molecular weight of 2000 g / mol, and a molecular weight distribution (PDI) of less than 1.5.

[0017] Please see Figure 1 This invention provides a high-adhesion, UV-resistant polyester powder coating and its preparation method, the technical solution of which is as follows: Example 1 Add 380 parts of terephthalic acid, 120 parts of isophthalic acid, and 40 parts of dodecanoic acid to an esterification reactor and stir until homogeneous. Then, add 380 parts of neopentyl glycol, 10 parts of trimethylolpropane, and 1.5 parts of stannous oxalate while stirring at 300 rpm. Purge with high-purity nitrogen and purge air. Increase the temperature to 220°C at a programmed rate of 8°C / min and maintain the temperature for 3 hours until the material is completely clear and transparent. A sample is taken and the acid value is measured to be <10 mg KOH / g. At this point, the material becomes a clear and transparent melt, and the reaction system is obtained. Cool the reaction system to 190°C at a rate of 4°C / min. Under 200 rpm conditions, slowly add 20 parts of terminal hydroxyl polydimethylsiloxane dropwise using a peristaltic pump over a total addition time of 30 minutes. After the addition is complete, add reactive UVA. 20 parts were heated to 200℃ under nitrogen protection and subjected to transesterification at 250 rpm for 2 hours. The melt was clarified to obtain a mixed system. The mixed system was heated from 200℃ to 240℃ at a rate of 2℃ / min. Under stirring at 300 rpm, a vacuum was applied for 40 minutes, and the vacuum degree was gradually reduced from -0.02 MPa and kept below -0.095 MPa. The polycondensation reaction was carried out to obtain a polycondensation product. The polycondensation product was stopped and the vacuum was maintained. Nitrogen protection was introduced and the temperature was reduced to 180℃ at a rate of 5℃ / min. Under stirring at 200 rpm, 50 parts of trimellitic anhydride were added, the stirring speed was increased to 300 rpm, and the reaction was kept at the temperature for 60 minutes. The product was then rapidly discharged to a preheated tablet press under nitrogen pressure. The discharge roller was used and the roller temperature was controlled at 15℃. The product was quenched and formed into tablets with a thickness of 2 mm. After crushing, the product was sealed and stored under nitrogen to obtain modified polyester resin. Add 300 parts of rutile titanium dioxide and 25 parts of precipitated barium sulfate to a high-speed mixer with a cooling jacket, stir and disperse at 800 rpm, start the cooling system, and control the temperature to not exceed 40℃ to obtain a mixed filler. Add 6 parts of epoxy silane coupling agent slowly and evenly dropwise into the high-speed rotating filler vortex using a peristaltic pump, controlling the addition time to 5-8 minutes, and maintain stirring at 600 rpm for 10 minutes to obtain the treated filler. Add 600 parts of modified polyester resin, 35 parts of HAA, 5 parts of HALS, the treated filler, and polyacrylate leveling agent WL-3090. Five parts of benzoin and five parts of benzoin were added to a high-speed mixer at 1200 rpm and premixed for 5 minutes. The mixer temperature was controlled at 35°C to obtain a powder system. The powder system was then fed evenly into a co-rotating twin-screw extruder via a vibrating feeder at 500 rpm, maintaining an extrusion rate of 8 kg / h, a pressure of 6 MPa, and a total residence time of 45 s to obtain a melt system. The melt system was then pressed into sheets using a 10°C water-cooled roller to obtain sheets with a thickness of 2 mm. The sheets were then added to a grinding mill and ground at 8000 rpm, followed by filtration through a 140-mesh filter. Finally, iron was removed by magnetic separation to obtain a polyester powder coating.

[0018] Examples 2-4 follow the same preparation method and parameters as Example 1, with differences shown in Table 1.

[0019] Table 1. Parameter variations in Examples 1-4 Comparative Example 1: Refer to Example 1, except that dodecanoic acid is not used in the modified polyester resin, and the amounts of the other components are adjusted accordingly.

[0020] Comparative Example 2 is the same as Example 1, except that only terephthalic acid is used in the modified polyester resin, and isophthalic acid is not added in combination. The amount of other components is adjusted accordingly.

[0021] Comparative Example 3 is the same as Example 1, except that trimethylolpropane is not added to the modified polyester resin, while the amounts of the other components remain unchanged.

[0022] Comparative Example 4 is the same as Example 1, except that terephthalic acid and neopentyl glycol are used as reaction substrates in the modified polyester resin, while the amounts of other added components remain unchanged.

[0023] Comparative Example 5 is the same as Example 1, except that trimellitic anhydride is not added to the modified polyester resin, while the amounts of the other components remain unchanged.

[0024] Comparative Example 6 is the same as Example 1, except that hydroxyl-terminated polydimethylsiloxane is not added to the modified polyester resin, and the amounts of the other components are adjusted accordingly.

[0025] Comparative Example 7 is the same as Example 1, except that the modified polyester resin is prepared by direct mixing and polymerization reaction without stepwise reaction process.

[0026] Comparative Example 8 is the same as Example 1, except that precipitated barium sulfate is not added in the preparation of the polyester powder coating, while the amounts of the other components remain unchanged.

[0027] Comparative Example 9 is the same as Example 1, except that precipitated barium sulfate and rutile titanium dioxide are not added in the preparation of the polyester powder coating, while the amounts of the other components remain unchanged.

[0028] Experimental Example 1: Mechanical Property Testing The polyester powder coatings prepared in Examples 1-4 and Comparative Examples 1-9 were electrostatically sprayed onto 0.5 mm thick cold-rolled steel plates pretreated with phosphate at 80 kV, with a film thickness of approximately 80 μm. After baking at 200 °C for 10 min, the coatings were allowed to cool naturally to room temperature. The hardness was tested according to the pencil hardness method of GB / T 6739-2023. The impact strength was tested according to the falling ball impact method of GB / T 1732-2020 at a test height of 50 cm. The bending performance was tested according to GB / T 6742-2021, with a smaller shaft diameter indicating better flexibility. The test results are shown in Table 2.

[0029] Table 2 Performance test results of the examples and comparative examples As shown in Table 2, the mechanical properties of the powder coating obtained in the comparative example, through adjustments to the components and process, were significantly reduced compared to the example. In Comparative Example 1, dodecanoic acid provided long, flexible carbon chain segments; its absence resulted in excessive rigidity of the polyester main chain, high internal stress, and although the hardness was relatively high, the material exhibited extreme brittleness, with a sharp decrease in impact strength and flexural properties. Comparative Example 2 shows that isophthalic acid is typically used to break down the high crystallinity of terephthalic acid, improving the resin's solubility and melt flowability. Using only PTA leads to excessively high resin crystallinity and melt flowability. The poor flowability makes it difficult to completely wet and level the film during film formation, resulting in defects inside the coating and reduced flexibility. In Comparative Example 3, trimethylolpropane (TMP), a trifunctional monomer used as a branching agent, leads to a more linear resin molecular structure and a lower crosslinking density during curing. Macroscopically, this manifests as decreased film hardness, impaired chemical resistance and density, poor overall balance, and a tendency for localized stress concentration due to weak energy dispersion. In Comparative Example 4, the lack of polyols and long-chain acids results in a single reaction substrate, preventing the formation of a branched-flexible network and leading to a decrease in overall mechanical properties. Simultaneously, the main chain flexibility... Excessive hydroxyl content without branching support leads to easy deformation of the coating film. Comparative Example 5 shows that trimellitic anhydride, added in the final stage of the process, is used for end-capping and provides carboxyl functionality, serving as a key active site for reaction with the curing agent. The absence of TMA results in an excessively low resin acid value, a severe lack of curing reaction sites, and the coating's inability to effectively cross-link and cure, leading to extremely low hardness, softness, and poor overall mechanical properties. In Comparative Example 6, hydroxyl-terminated polydimethylsiloxane has low surface energy, providing excellent leveling and surface smoothness, and releasing curing stress. Its absence results in a high coefficient of friction on the coating surface, reducing scratch resistance. The force decreased, and the internal stress caused the impact resistance to be worse than in the examples. Combined with the results of Comparative Example 7, it can be seen that direct mixing reaction will cause PDMS and TMA to be randomly distributed in the molecular chain, and cannot form a soft and hard block structure. Moreover, TMA may be wrapped in the chain rather than at the end, resulting in reduced curing activity and disruption of the overall mechanical property balance. In Comparative Examples 8-9, precipitated barium sulfate and titanium dioxide were treated with silane coupling agent, which played a skeleton reinforcement role in the coating. After their absence, although the flexibility was improved, the hardness and rigidity were significantly reduced, and the physical shielding performance provided by pigments and fillers was lost.

[0030] In summary, this invention utilizes terephthalic acid to provide a rigid framework, isophthalic acid to reduce crystallinity, and dodecanoic acid to introduce long-chain flexibility. The gradient ratio of these three components controls the Tg and crosslinking density, ensuring a balance between hardness and toughness. Trimethylolpropane is introduced into the modified polyester resin to control branching and prevent excessive linear chain extension. Trimethylolpropane precisely controls the acid value and synergistically forms dense crosslinks with HAA / HALS, preventing microcrack propagation. The introduction of terminally hydroxyl polydimethylsiloxane via transesterification introduces flexible side chains, improving interfacial lubrication and compatibility, reducing internal friction, preventing phase separation, and enhancing impact resistance. The use of epoxy silane coupling agents to treat inorganic fillers allows stress to be effectively transferred and dissipated between the resin and filler under impact, further enhancing the mechanical strength of the coating film. Finally, a stepwise polymerization process combines the flexibility of organosilicon, the toughness of long-chain fatty acids, and the rigidity of aromatic polyesters, while TMA end-capping ensures high crosslinking density, ultimately achieving a balance between high hardness and high impact resistance.

[0031] Comparative Examples 5-7 were prepared using the same methods and parameters as in Example 1, with differences shown in Table 3.

[0032] Table 3. Parameter changes in Examples 1, 5-7 Comparative Example 10 is the same as Example 1, except that reactive UVA is not added to the modified polyester resin, while the other components remain unchanged.

[0033] Comparative Example 11 is the same as Example 1, except that the reactive UVA is added during the preparation of the modified polyester resin but during the preparation of the powder coating through melt mixing.

[0034] Comparative Example 12 is the same as Example 1, except that HALS is not added, while the other amounts remain unchanged.

[0035] Comparative Example 13 is the same as Example 1, except that reactive UVA and HALS are not added, while the other amounts remain unchanged.

[0036] Experiment Example 2: UV Resistance Test The powder coatings obtained in Examples 1, 5-7, and Comparative Examples 2, 4, 6-8, and 10-13 were sprayed and tested according to the procedure in Experimental Example 1. The initial impact strength was tested according to the method in Experimental Example 1, and an accelerated aging chamber (QUV) was used with a UVA-340 lamp at an irradiance of 0.68 W / m²@340 nm, 8 hours of UV exposure followed by 4 hours of condensation at 60°C. Tests were conducted for 500 hours, 1000 hours, and 2000 hours to determine the impact strength and calculate the strength retention rate. The test results are shown in Table 4. The change in impact strength retention rate of the powder coatings prepared in Examples 1, 6-8, and 10-13 with light exposure time is shown in Table 4. Figure 1 As shown.

[0037] Table 4 Test results of the examples and comparative examples As shown in Table 4, the UV resistance of the powder coating obtained in the comparative examples, through adjustments to the components and process, was significantly reduced compared to the examples. Comparative Example 2 showed that the absence of isophthalic acid increased the number of resin crystalline regions, leading to preferential photodegradation at grain boundaries, rapid free radical diffusion, and consequently, early strength reduction, long-term yellowing / embrittlement of the coating, and damage to the main chain ester bonds due to the accumulation of photo-oxidation products. In Comparative Example 4, the lack of branched / flexible components prevented the formation of a stable network to support UVA / HALS. The single substrate resulted in low molecular weight, resulting in deep UV penetration and low retention due to the absence of branched components. The fixed antioxidants at the chemical point, combined with thermal aging, accelerate chain breakage and reduce UV resistance. Comparative Example 6 shows that siloxanes introduce flexible side chains through transesterification, improving UVA compatibility and surface shielding. However, the absence of these side chains leads to uneven UVA distribution, high surface friction, and easy localized oxidation from UV radiation, resulting in decreased retention. Furthermore, the lack of a lubricating layer causes free radicals to accumulate at the interface, amplifying photodegradation. Combined with Comparative Example 7, the stepwise process ensures chemical intercalation of UVA during the transesterification stage, preventing migration. Direct mixing results in physical encapsulation of UVA, making it prone to precipitation under heat / light, reducing activity, and causing low long-term retention due to the block structure. The lack of a structure prevents UVA from effectively capturing deep free radicals, accelerating internal degradation of the coating. Comparative Example 8 shows that barium sulfate and titanium dioxide synergistically scatter UV, enhancing physical shielding and preventing photochemical reactions from concentrating in the resin matrix. Comparative Example 10 shows that reactive UVA absorbers are the main components protecting polymers from UV damage. The absence of reactive UVA leads to easy breakage of the polyester main chain or the generation of free radicals under UV light, resulting in rapid chalking and yellowing of the coating. Macroscopically, this manifests as a sharp decline in mechanical properties after aging and extremely low retention. Comparative Example 11 shows that non-reactive UVA... A, which is not bonded to polyester, is prone to migration, precipitation, and volatilization during long-term outdoor use, causing the protective effect to fail over time. In contrast, reactive UVA is fixed to the molecular chain through chemical bonds, achieving long-term anti-aging. Combined with the results of Comparative Examples 12-13, it can be seen that the lack of HALS leads to the inability to effectively remove free radicals caused by photo-oxidation, which accelerates the degradation of the coating and reduces the impact resistance. By utilizing a dual anti-aging protection mechanism, through the synergistic effect of absorbing ultraviolet rays and removing free radicals, and taking advantage of the long-term effect of reactive UVA, the anti-UV aging performance is significantly improved.

[0038] In summary, this invention utilizes a stepwise polymerization process to covalently bond reactive UVA to the polyester backbone via transesterification, ensuring long-term, high-intensity UV absorption through an anchoring mechanism. The synergistic effect of HALS in scavenging free radicals generated by photo-oxidation provides comprehensive protection from source blocking to process extinguishing. The introduced long-chain flexible DDDA and flexible PDMS side chains act as buffers within the molecular chain, effectively reducing curing stress and increasing molecular free volume and mobility. During aging, they better resist embrittlement caused by polymer degradation and delay the propagation of microcracks. The branching degree controlled by TMP and the high acid value regulated by TMA ensure the formation of a high-density, uniform network structure during crosslinking with HAA. By combining the long-term protection of chemical bonding with the inherent stability of the molecular structure, the coating maintains excellent impact strength, achieving a synergistic balance between high mechanical properties and long-term UV resistance.

[0039] Comparative Example 14 is the same as Example 1, except that no epoxy silane coupling agent is added during the preparation of the polyester powder coating, while the amounts of the other components remain unchanged.

[0040] Comparative Example 15 is the same as Example 1, except that the epoxy silane coupling agent is not pretreated and is directly melted with the other components at low temperature.

[0041] Comparative Example 16 is the same as Example 1, except that no hydroxyl-terminated polydimethylsiloxane is added to the modified polyester resin, no epoxy silane coupling agent is added in the powder coating preparation, and the amounts of other components remain unchanged.

[0042] Experiment Example 3 Adhesion Performance Test The powder coatings obtained in Examples 1, 5-7, 6-7, and 14-16 were sprayed and naturally cooled according to the process in Experimental Example 1. Following GB / T 9286-2021, the cross-cut test was conducted at 30°C, with a spacing of 6 mm and a blade width of 1 mm. Grade 0 was the best (no peeling), and Grade 5 was the worst (more than 65% peeling). For water resistance, the samples were immersed in boiling water for 168 hours, then removed and subjected to a cross-cut test at 30°C for 1 hour. Specific test results are shown in Table 5.

[0043] Table 5 Test Results of Examples and Comparative Examples As shown in Table 5, the adhesion performance of the powder coating obtained by adjusting the components and process in the comparative examples was significantly reduced compared to the examples. In Comparative Example 6, the hydroxyl-terminated polydimethylsiloxane introduced flexible side chains through transesterification, improving the wettability of the resin to the substrate and the surface energy matching, and reducing the interfacial tension. After its absence, the resin polarity was too high, the phosphate layer and the coating film were weakly bonded, the adhesion at room temperature was reduced, there was no flexible buffer during boiling, water molecule penetration accelerated interfacial hydrolysis, and the coating film was easily peeled off due to the small free volume. The results of Comparative Example 7 show that the stepwise process ensured the gradient embedding of siloxane / TMA, forming a uniform block structure and promoting the entanglement of molecular chains with the substrate. Direct mixing led to random distribution of components, causing phase separation and uneven interface. Under boiling conditions, thermal stress amplified defects, water vapor induced microbubbles, and due to the lack of ordered bonding, the adhesion sites were reduced, resulting in a significant decrease in adhesion. In Comparative Example 14, the absence of the coupling agent led to... Poor compatibility between the filler and the resin matrix creates a weak interface, resulting in stress concentration points within the coating. During boiling, water molecules preferentially penetrate from these weak interfaces to the substrate surface, disrupting interfacial bonding and causing a sharp decline in water resistance. Comparative Example 15 shows that the coupling agent needs to be pre-treated by being uniformly and slowly added to the filler under high-speed stirring to ensure complete hydrolysis and the formation of a monolayer covering the filler surface. Direct melting and mixing without pretreatment prevents the coupling agent from effectively and uniformly covering the filler; most of the coupling agent may directly participate in resin crosslinking or exist in a free state, resulting in low interfacial bonding efficiency and significantly reduced adhesion. Comparative Example 16 shows that the double deficiency disrupts the flexible modification and filler interface, doubly weakening adhesion and significantly reducing adhesion. Without buffering and anchoring effects during boiling, water molecules directly reach the substrate, leading to a lack of synergy between the resin, filler, and substrate phases. This synergistic effect of heat and humidity induces large-area delamination, resulting in overall reduced adhesion.

[0044] In summary, the branching degree controlled by trimethylolpropane and the high acid value precisely regulated by trimellitic anhydride in this invention, combined with HAA, form a high-density, dense, and uniform cross-linked network, effectively preventing moisture penetration to the coating-substrate interface and ensuring hydrolysis and boiling resistance. The epoxy silane coupling agent, through pretreatment, forms a uniform active layer on the surface of the inorganic filler and, during curing, covalently bonds to the polyester matrix via epoxy groups, achieving a strong chemical bond between the filler, resin, and substrate. This effectively transfers and dissipates impact stress from the resin to the filler, significantly enhancing interfacial bonding strength. Simultaneously, the low surface energy of PDMS is introduced to synergistically improve the wetting and spreading ability of the powder melt on the substrate, increasing initial adhesion. Through the flexible embedding of siloxane ester exchange, silane pretreatment and filler bridging, stepwise polymerization of ordered blocks, component synergy of a branched-end-capped dense network, and process optimization of gradient heating and rapid cooling, excellent coating adhesion is achieved, significantly enhancing substrate bonding stability, making it suitable for high-durability outdoor powder coatings.

[0045] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a high-adhesion, UV-resistant polyester powder coating, characterized in that, Includes the following steps: Rutile titanium dioxide and precipitated barium sulfate are stirred and dispersed, then an epoxy silane coupling agent is added and stirred to obtain a treated filler. 580-620 parts of modified polyester resin, 30-35 parts of HAA, 3-8 parts of HALS, the treated filler, and additives are added to a high-speed mixer and mixed to obtain a powder system. The powder system is uniformly fed into a co-rotating twin-screw extruder and melt-extruded to obtain a melt system. The melt system is water-cooled, pressed into sheets, ground, sieved, and magnetically separated to remove iron, thus obtaining the polyester powder coating. The modified polyester resin is obtained by esterification, transesterification and polycondensation of mixed acid, neopentyl glycol, reactive UVA, polymeric monomer and hydroxyl-terminated polydimethylsiloxane, followed by end-capping with an end-capping agent, and then quenching and pulverizing. The mixed acid is obtained by mixing terephthalic acid, isophthalic acid, and dodecanoic acid; the polymer monomer is trimethylolpropane; the end-capping agent is trimellitic anhydride; and the additives include polyacrylate leveling agents and benzoin. The preparation of the treatment filler includes the following steps: 300 parts of the rutile titanium dioxide and 20-30 parts of the precipitated barium sulfate are stirred and dispersed, and the temperature is controlled not to exceed 40°C to obtain a mixed filler; 5-8 parts of the epoxy silane coupling agent are added dropwise to the mixed filler using a peristaltic pump, and the addition time is controlled to be 5-8 minutes, and the mixture is stirred to obtain the treatment filler. The preparation of the modified polyester resin includes the following steps: 350-400 parts of terephthalic acid, 100-150 parts of isophthalic acid, and 30-50 parts of dodecanoic acid are added to an esterification reactor and stirred until homogeneous. Then, 350-400 parts of neopentyl glycol, 8-15 parts of trimethylolpropane, and 1-2 parts of stannous oxalate are added. Nitrogen gas is introduced, and the temperature is raised to 210-230°C and maintained for esterification to obtain a reaction system. The reaction system is cooled to 190°C at a rate of 3-5°C / min, and 15-30 parts of terminal hydroxyl polydimethylsiloxane are added dropwise. Then, 15-30 parts of reactive UVA are added, and the temperature is raised to 200°C under nitrogen protection to obtain a mixed system. The mixed system is stirred and subjected to vacuum to induce a polycondensation reaction until the viscosity of the system reaches 2500-3500 ppm. The polycondensation product was obtained at mPa·s; the polycondensation product was then added to 45-55 parts of trimellitic anhydride under nitrogen protection and stirring conditions, and the reaction was carried out at a constant temperature; the product was then pressurized with nitrogen, quenched and sheeted, and the sheet was crushed to 1-2 mm to obtain the modified polyester resin.

2. A high-adhesion, UV-resistant polyester powder coating, characterized in that, The product comprises rutile titanium dioxide, precipitated barium sulfate, epoxy silane coupling agent, modified polyester resin, HAA, HALS, and additives; the modified polyester resin is obtained by covalently modifying hydroxyl-terminated polydimethylsiloxane and reactive UVA, and then end-capping with trimellitic anhydride; the polyester powder coating is prepared by the preparation method described in claim 1.

Citation Information

Patent Citations

  • High-transparency weather-resistant polyester resin and preparation method thereof

    CN119371645A